Mithridates Ier et Suse - Gaslain, Jérôme (Anabasis. Studia Classica et Orientalia, 2010)
During the reign of Mithradates I (165–132 B.C.), the Arsacid kingdom became a great empire, after its conquests in Central Asia, Media, Mesopotamia and part of Iran. This expansion had only been possible because the Arsacid king payed much attention to the method used to lay hands, either militarily or diplomatically, on the cities of these territories. The seizure of Susa offers a good illustration of this point .